2013
DOI: 10.4028/www.scientific.net/kem.587.325
|View full text |Cite
|
Sign up to set email alerts
|

Socket Preservation Procedure after Tooth Extraction

Abstract: Jaw deformities from tooth removal can be prevented and repaired by a procedure called socket preservation. Socket preservation can greatly improve the smile’s appearance and increase the chances for successful dental implants for years to come. The procedure begins with atraumatic tooth extraction. Every attempt is made to preserve the surrounding bone and soft tissue, with an emphasis on being careful not to fracture the delicate buccal plate. There are a number of techniques and instruments that aid in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…2 Pain, infection, bone loss, or fracture of the tooth are the most common reasons for the extraction of teeth. 3 Once the tooth is extracted, the alveolar bone that holds the tooth in place (the socket) is often damaged or undergoes a three-dimensional bone resorption. And the resorption is lifelong, irreversible, chronic, and cumulative.…”
Section: Introductionmentioning
confidence: 99%
“…2 Pain, infection, bone loss, or fracture of the tooth are the most common reasons for the extraction of teeth. 3 Once the tooth is extracted, the alveolar bone that holds the tooth in place (the socket) is often damaged or undergoes a three-dimensional bone resorption. And the resorption is lifelong, irreversible, chronic, and cumulative.…”
Section: Introductionmentioning
confidence: 99%
“…In a 30-patient clinical study, the use of biomaterials reduced horizontal loss, but not vertical loss, of the buccal wall [11]. Other studies have demonstrated that vertical bone loss was limited using an allograft covered with a resorbable collagen membrane [1012131415161718]. Clearly, biomaterials delay osseointegration during the time of reossification during new bone-implant contact.…”
Section: Introductionmentioning
confidence: 99%
“…Pure cortical allograft particles provide the density and strength of an autograft of cortical bone without the cost or invasiveness of that method. Therefore, the renewed interest of clinicians in allografts, with or without a collagenous membrane, justifies new in-depth studies of this material [131518]. Our study focused on cortical bone chips, which have not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Socket preservation helpsto maintain the alveolar architecture and significantly reduces the loss ofridge width and height following tooth removal [22].…”
Section: Key Engineering Materials Vol 614mentioning
confidence: 99%